Microfinance in Pesantren: A Note - Ali, Mohammad Mahbubi; Rahayu, Solihah Sari (The Economic Review of Pesantren, 2024)
This study aims to see the development of research on the topic of "Microfinance and Pesantren" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Microfinance and Pesantren" which comes from the Dimension database with a total of 30 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of research development "Microfinance and Pesantren" in the world. The results of the study found that there were 4 clusters with the most used words being pesantren, development, Islamic microfinance, community, Islamic boarding school, Islamic microfinance institution, and micro waqf bank. Then, the topics of research paths related to Microfinance and Pesantren are Pandemic and Micro Waqf Bank Sustainability in Pesantren, Islamic Microfinance as a Solution to Poverty, Independence of Pesantren and Pesantren Microfinance, and Implementation of Islamic Microfinance in Pesantren.